Measuring Financial Literacy of Young Adults in The Digital Economy: A Gender Perspective - lestari, dwi indah (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aim to assess young adults' financial literacy and determine whether financial literacy differs between males and females. Additionally, this study examines whether students in the Faculty of Economics and Business are more financially literate than those in other faculties. This research using a survey approach where data collection is conducted through questionnaires. The target population includes students aged 18 to 22 from various universities across Java. Respondents were selected through a census method. In this study, we collected 333 respondents with valid data of 331 respondents. The data analysis method includes descriptive analysis and confirmatory analysis. The result of this study shows that money attitude does not significantly influence financial literacy; however, after being analyzed per dimension, the avoidance and reward dimensions significantly influence financial literacy. Gender does not positively influence Financial Literacy, and no disparities in financial literacy among students with exposure to financial education and those without such exposure.